Laser‐Induced Graphene: From Discovery to Translation. Issue 1 (4th October 2018) - Ye, Ruquan; James, Dustin K.; Tour, James M.
Abstract: Laser‐induced graphene (LIG) is a 3D porous material prepared by direct laser writing with a CO2 laser on carbon materials in ambient atmosphere. This technique combines 3D graphene preparation and patterning into a single step without the need for wet chemical steps. Since its discovery in 2014, LIG has attracted broad research interest, with several papers being published per month using this approach. These serve to delineate the mechanism of the LIG‐forming process and to showcase the translation into many application areas. Herein, the strategies that have been developed to synthesize LIG are summarized, including the control of LIG properties such as porosity, composition, and surface characteristics, and the advancement in methodology to convert diverse carbon precursors into LIG. Taking advantage of the LIG properties, the applications of LIG in broad fields, such as microfluidics, sensors, and electrocatalysts, are highlighted. Finally, future development in biodegradable and biocompatible materials is briefly discussed. Abstract : Laser‐induced graphene is a 3D porous graphene material synthesized by laser irradiation on commercial polymers or natural materials using a CO2 infrared laser under ambient conditions. This method presents advantages over the traditional 3D graphene synthesis. Recent progress in synthesis and application, and perspectives for future opportunities are highlighted.